Year 2000 compliance test specifications : strategic guidelines and methodologies - Malta Information Technology & Training Services L (MITTS Blata I-BajdaMT, 1998)
Lays out the strategy to be followed by MITTS Limited as part of the year-2000 project. Covers both hardware and software testing.